Francesco Benozzo, The Ridge and the Song. Sailing the Archipelago of Poetry Preface by Antonella Riem Natale (Altre Modernità, 2024)
Francesco Benozzo, The Ridge and the Song. Sailing the Archipelago of Poetry Preface by Antonella Riem Natale(Udine, Forum, 2022, 32 pp. ISBN 978-8832833416)by Saverio Tomaiuolo